2015
DOI: 10.1037/xge0000043
|View full text |Cite
|
Sign up to set email alerts
|

If all your friends jumped off a bridge: The effect of others’ actions on engagement in and recommendation of risky behaviors.

Abstract: There is a large gap between the types of risky behavior we recommend to others and those we engage in ourselves. In this study, we hypothesized that a source of this gap is greater reliance on information about others' behavior when deciding whether to take a risk oneself than when deciding whether to recommend it to others. To test this hypothesis, we asked participants either to report their willingness to engage in a series of risky behaviors themselves; their willingness to recommend those behaviors to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 22 publications
8
23
0
Order By: Relevance
“…4 , participants played riskier on a given trial if their previous safe choice was accompanied with loss (on the previous trial), again indicating strategic decision making. Overall, our results are consistent with the notion that the influence of others’ choices on risky behavior is important 13 . Thus, our findings overall suggest that information about peer choices is sufficient to alter one’s own risky behavior.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…4 , participants played riskier on a given trial if their previous safe choice was accompanied with loss (on the previous trial), again indicating strategic decision making. Overall, our results are consistent with the notion that the influence of others’ choices on risky behavior is important 13 . Thus, our findings overall suggest that information about peer choices is sufficient to alter one’s own risky behavior.…”
Section: Discussionsupporting
confidence: 90%
“…First, analysis of longitudinal and network data 11 , 12 , 19 , 23 has shown that changes in the behavior of one member of a social network can produce similar changes in the behavior of other members 11 , 12 , 19 , 23 . Second, analysis of self-report measures has shown that the influence of others’ choices on risky behavior outweighs any influence due to changes in one’s perceptions of the benefits and costs of the risky behavior 13 . Third, analysis of behavioral measures of peer susceptibility has shown that peers can influence choices by providing explicit suggestions encouraging riskier play 20 22 , 24 , 25 or by their mere presence 15 18 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…These factors can be further collapsed to describe desirable (thrill-seeking) and undesirable (reckless, rebellious, and antisocial) behaviours. An adult study similar in the design to this current study found opposite patterns of engagement and recommendation for the "desirable" and the "undesirable" risk behaviours (Helfinstein et al, 2015). Further it has recently been proposed that this distinction provides a more relevant framing for understanding adolescent risk taking (Duell & Steinberg, 2019), we therefore applied this distinction in our analyses as well.…”
Section: Methodsmentioning
confidence: 81%
“…In one recent study, it appeared as if adults used perceived social norms as heuristics to judge whether risky behaviours are appropriate when engaging in them. In turn when recommending, it appeared as if people took the associated risks more into account (Helfinstein et al, 2015). Based on these previous findings we expected subjects would be more likely to engage in risky behaviours themselves than to recommend them to others.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation